The mediating role of trait anxiety in the relationship between cyberbullying, depression, and suicidal ideation - Laith Hilal Taqi , Lect. (lark, 2025)
This study addresses the mediating role of anxiety as a trait in the relationship between cyberbullying, depression, and thoughts of suicide among secondary school students in the city of Wasit. The research was designed as a descriptive study of the correlation type, based on structural equation modeling. The sample included all secondary school students in the city. Randomly selecting 250 students, with 50 students selected from each of 10 existing schools (5 girls' schools and 5 boys' schools), participants completed the Cyberbullying Questionnaire (2009), the Spielberger Trait Anxiety Test (STAI), and the Beck Depression Questionnaire (short version) ( BDI-S), and the Suicidal Ideation Questionnaire (BSSI). The data were analyzed by calculating correlation coefficients and structural equation modeling using SPSS-26 and AMOS-24. The results showed that the presented model had a good fit. The results also showed that cyberbullying is related to depression and suicidal thoughts through anxiety as a trait. The results of this study can help In better understanding cyberbullying and its effects on adolescents, which helps health professionals early identify adolescents at risk and provide them with the necessary support
Keywords: anxiety, cyberbullying, depression, thoughts of suicide.